2024
DOI: 10.3390/cells13100868
|View full text |Cite
|
Sign up to set email alerts
|

Individually Cultured Bovine Zygotes Successfully Develop to the Blastocyst Stage in an Extremely Confined Environment

Angela Travaglione,
Andrea Candela,
Vincenza De Gregorio
et al.

Abstract: The possibility of detecting the developmental competence of individually cultured embryos through analysis of spent media is a major current trend in an ART setting. However, individual embryo culture is detrimental compared with high-density group culture due to the reduced concentration of putative embryotropins. The main aim of this study was to identify an individual culture system that is not detrimental over high-density group culture in the bovine model. Blastocyst rates and competence were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
0
0
Order By: Relevance
“…The beneficial effects of confinement in culture systems that avoid the harmful exchanges between oil and medium in reduced volumes microdrops was also elegantly shown by Thouas et al (2003) [148] which cultured two mouse embryos in 1 µL glass capillaries achieving blastocyst cell numbers similar to those observed in high-density group culture with 20 zygotes in 10 µL drops under oil. Recently, Travaglione et al (2024) showed that extreme confinement of individually cultured bovine embryos in ~70 nl microwells improved blastocyst rates compared to both conventional group culture (50 embryos/ 500 µL) and semi-confined group culture in microwell chambers (16 embryos/60 µL) [149]. Other studies showed that the spacing among embryos in high-density group cultures is critical.…”
Section: In Vitro Embryo Culture: Individual Versus Group Culturementioning
confidence: 99%
“…The beneficial effects of confinement in culture systems that avoid the harmful exchanges between oil and medium in reduced volumes microdrops was also elegantly shown by Thouas et al (2003) [148] which cultured two mouse embryos in 1 µL glass capillaries achieving blastocyst cell numbers similar to those observed in high-density group culture with 20 zygotes in 10 µL drops under oil. Recently, Travaglione et al (2024) showed that extreme confinement of individually cultured bovine embryos in ~70 nl microwells improved blastocyst rates compared to both conventional group culture (50 embryos/ 500 µL) and semi-confined group culture in microwell chambers (16 embryos/60 µL) [149]. Other studies showed that the spacing among embryos in high-density group cultures is critical.…”
Section: In Vitro Embryo Culture: Individual Versus Group Culturementioning
confidence: 99%